2016
DOI: 10.1111/pedi.12416
|View full text |Cite
|
Sign up to set email alerts
|

Insulin pump therapy in children with type 1 diabetes: analysis of data from the SWEET registry

Abstract: Background Intensified insulin delivery using multiple daily injections (MDI) or continuous subcutaneous insulin infusion (CSII) is recommended in children with type 1 diabetes (T1D) to achieve good metabolic control. Objective To examine the frequency of pump usage in T1D children treated in SWEET (Better control in Paediatric and Adolescent diabeteS: Working to crEate CEnTers of Reference) centers and to compare metabolic control between patients treated with CSII vs MDI. Methods This study included 16 570 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 29 publications
6
86
3
4
Order By: Relevance
“…The use of CSII is increasingly common in the modern management of children and adults with Type 1 diabetes, allowing them to manage their diabetes intensively and optimize glycaemic control . While CSII offers advantages over traditional insulin delivery systems by providing greater flexibility in the timing of meals and snacks, it still does not protect the patient from hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CSII is increasingly common in the modern management of children and adults with Type 1 diabetes, allowing them to manage their diabetes intensively and optimize glycaemic control . While CSII offers advantages over traditional insulin delivery systems by providing greater flexibility in the timing of meals and snacks, it still does not protect the patient from hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the US‐based type 1 diabetes exchange (T1DX) registry focusing on children <6 years demonstrated lower HbA1c levels for those on pumps, with a tendency for lower HbA1c levels prior to pump initiation, suggesting selection of an ideal population for pump use may have occurred . The SWEET (better control in Pediatric and Adolescent Diabete S: W orking to create C E n T ers of Reference) centers found that almost half of the 16 000 registry participants used pumps, and this technology was associated with lower HbA1c and daily insulin dose as compared to MDI . In a cross‐sectional comparison of three large, transatlantic registries, which included the US‐based T1DX, the German/Austrian Prospective Diabetes Follow‐up Registry (DPV), and the English/Welsh National Pediatric Diabetes Audit (NPDA), a pooled analysis of nearly 55 000 pediatric participants, pump use was associated with lower mean HbA1c (pump 8.0% ± 1.2% vs injection: 8.5% ± 1.7%, P < 0.001) .…”
Section: Insulin Pumpsmentioning
confidence: 99%
“…Over the last decade, the use of insulin pump therapy in the pediatric age group has markedly increased . In two recently published cross‐sectional studies that explored data from two large registries, insulin pump therapy was reported to be superior for glycemic control compared to multiple daily injections (MDI) . However, there is limited data on the long‐term outcomes (glycemic outcomes as well as acute complications) of insulin pump therapy in a real‐world population‐based setting.…”
Section: Introductionmentioning
confidence: 99%